Adsorption Studies on the Removal of Hexavalent Chromium-Contaminated Wastewater Using Activated Carbon and Bentonite - Abdel Wanees, Salah; Monem M. Ahmed, Abdel; S. Adam, Mohamed; A. Mohamed, Mamdouh (Asian Journal of Chemistry, 2013)
In this study, the adsorption potential of activated carbon and bentonite for removal of Cr(VI) ions from wastewater has been investigated. The study involves batch type experiments to investigate the effect of initial concentration, adsorbent dose, agitation speed, contact time, temperature and pH of solution on adsorption process and the optimum conditions were evaluated. The adsorption process has fit pseudo-second order kinetic models. Langmuir and Freundlich adsorption isotherm models were applied to analyze adsorption data and both were found to be applicable to this adsorption process. Thermodynamic parameters, e.g., DGº, DSº and DHº of the on-going adsorption process have also been calculated and the sorption process was found to be endothermic. Finally, it can be seen that bentonite was found to be more effective for the removal of Cr(VI) than activated carbon, under the same experimental conditions.